The additive antiplatelet action of clopidogrel in patients with coronary artery disease treated with aspirin - Dropinski, Jerzy; Jakiela, Bogdan; Sanak, Marek; Wegrzyn, Wojciech; Biernat, Marta; Dziedzina, Sylwia; Plutecka, Hanna; Szczeklik, Andrew (Thrombosis and Haemostasis, 2007)
We searched for additional anti-platelet effects of clopidogrel in coronary artery disease (CAD) patients treated with aspirin. Response to clopidogrel was also stratified according to aspirin resistance. Out of 76 screened aspirin-treated CAD male patients, five were aspirin-resistant based on arachidonic acid (AA) and ADP aggregometry.These five patients and 15 aspirin-sensitive patients entered the proper study. Platelet function was assessed at baseline and after one week of additional clopidogrel treatment using aggregometry, flow cytometry (ADP, TRAP-6) and platelet reactivity index (PRI) based on VASP (vasodilatorstimulated phosphoprotein) expression.We evaluated the same markers in 15 healthy men after aspirin treatment. In healthy subjects aspirin did not affect resting or ADP-induced activated GPIIb/IIIa and P-selectin expression. The P-selectin expression on ADP-activated platelets was increased (p<0.01) in aspirin treated ASA-resistant CAD patients as compared to ASA-sensitive group or aspirin-treated healthy subjects. Clopidogrel significantly decreased ADP and AA-induced platelet aggregation and overcame aspirin resistance in four of five patients. Expression of ADP-induced activation markers was significantly lowered after clopidogrel in all patients.Out of 20 patients,five did not respond to clopidogrel (<10% inhibition of ADP aggregation), and this group showed no change in expression of ADPinduced activation markers after clopidogrel. Clopidogrel treatment significantly reduced PRI only in the clopidogrel-sensitive group. In conclusion, the addition of clopidogrel to aspirin provides greater inhibition of platelets and can overcome aspirin resistance. Flow cytometric analysis of platelets is useful for monitoring of clopidogrel therapy.
Keywords: Aggregation; aspirin; clopidogrel; flow cytometry; platelets